Possible pharmacological interactions in hypertensive and/or diabetic elderly in family health units at Blumenau (SC) - Vicente Codagnone Neto; Victor Pundek Garcia; Ernani Tiaraju de Santa Helena (Universidade de São Paulo, 2010)
The aim of this study was to examine the possible adverse drug-drug interactions in the elderly population (>60 years) diagnosed either with diabetes, arterial hypertension or both, at a Family Health Unit (FHU) clinic in Blumenau, state of Santa Catarina, Brazil. For this purpose 318 subjects were interviewed using a pretested form with social and demographic aspects regarding their disease and its complications. All drugs used by this population were grouped, and the drug-drug interactions were detected by using the "Drug Interaction Checker" software, and classified for frequency and severity. The average age of patients was 70.6 years, with a higher number of female patients (216; 67.9%). Most subjects were being treated for both diseases (149; 46.86%). Out of a total of 1,541 medications prescribed, the most prevalent were: hydrochlorothiazide (131; 8.4%) and enalapril maleate (130; 8.4%). A total of 295 possible drug-drug interactions were detected in 152 patients (1.9 interactions per subject), 275 (93.2%) moderate and 20 (6.8%) severe or highly severe. The possible interaction prevalence was 0.93 (0.55 to 1.40 depending on health unit). The most frequent possible interaction was that between acetylsalicylic acid and enalapril maleate (37; 12.5%). Patients had an average consumption of 6.6 drugs and 9.8% of subjects reported physical discomfort when using medicines. Elderly patients use many medications that could cause adverse reactions and possible drug-drug interactions, where this issue warrants closer attention of prescribers and health providers. Buscou-se identificar possíveis interações medicamentosas em pessoas idosas com diabetes melito (DM) e/ou hipertensão arterial sistêmica (HAS) sendo atendidas em unidades de Saúde da Família, em Blumenau (SC). Entrevistaram-se 318 pessoas com 60 e mais anos, portadoras de DM e/ou HAS, mediante questionário estruturado pré-testado, com variáveis sócio-demográficas da doença e do tratamento. As interações medicamentosas foram verificadas através do aplicativo "Drug Interaction Checker" e classificadas quanto a freqüência e severidade. A maioria dos pacientes era do sexo feminino (216; 67,9%), com média de idade de 70,6 anos (DP = 6,9), recebendo tratamento por ambas as doenças (149; 46,86%). Dentre 1.541 medicamentos prescritos, os mais prevalentes foram: hidroclorotiazida (131; 8,4%) e maleato de enalapril (130; 8,4%). Foram detectadas 295 possíveis interações medicamentosas em 152 idosos (média 1,9 interações), das quais (275; 93,2%) foram moderadas e (20; 6,8%) severas ou muito severas. A prevalência de possíveis interações foi de 0,93 (0,55 a 1,40, dependendo da unidade de saúde). A possível interação mais freqüente foi entre ácido acetilsalicílico e maleato de enalapril (37; 12,5%). Cada paciente fazia uso de 6,6 medicamentos em média e 9,8% relataram algum desconforto físico com o uso de medicamentos. Idosos utilizam grande quantidade de medicamentos que resultam em reações adversas e possíveis interações medicamentosas, merecendo maior atenção dos prescritores e gestores.